Does managerial coaching empower employees? – A psychoanalytical approach. Issue 1 (2nd January 2023) - Jepsen, Kim Sune Karrasch; Dehlholm, Mikkel
ABSTRACT: Managerial coaching is an important and arguably emblematic example of the transformation of managerial techniques that has occurred in the last decades, where more equal work relations and empowerment of employees is increasingly promoted. In the literature on managerial coaching, the role of the manager-coach is to open up a space for the employee to formulate her desires and attempt to clear the way for their realization. Tensions between the desire of employees and that of managers, although to some degree acknowledged in parts of the literature, is not sufficiently addressed. Furthermore, there is a marked lack of recognition of how the fact that coaching takes place in the context of hierarchical organizations, operating on markets with the aim of creating profit, affect the praxis of managerial coaching. We address these issues by conducting a Lacanian discourse analysis of managerial coaching literature, and show that it operates with a paradoxical notion of autonomy: The autonomy of employees is only called upon in so far as it can be aligned with the aims of management. Through a transposition of Lacan's four discourses, we furthermore situate the phenomena of managerial coaching in the context of the history of management forms. We argue that managerial coaching is emblematic of a shift from what Lacan calls the University discourse (under Taylorist management), to what is best understood as a semblance of the psychoanalytical discourse. It is only a semblance, since the manager-coach in reality retains the position of master in relation to employees.